Caracterização multiescalar e modelagem geológica de carbonatos neoproterozoicos da Formação Lagoa do Jacaré, Grupo Bambuí, na pedreira GMD - Paraopeba - MG: uma contribuição à geologia de reservatório - Alex Rodrigues de Freitas (2020)
The present work features multiscale analysis of Neoproterozoic carbonate rocks of Lagoa do Jacaré Formation (Bambuí Group) that outcrops in a deactivated quarry in Paraopeba - MG. The Multiscale Reservoir Characterization (CAMURES) methodology was partially applied, and it assumes as a premise the characterization of analogue outcrops using different investigative tools, in different scales of observation, ranging from basin scale, passing through reservoir scale, until petrophysics microscale. The rocks in GMD quarry comprise five sedimentary lithofacies: medium to fine grained massive calcarenites, intraclastic breaches, fine calcarenites with asymmetric ripple marks, medium grained calcarenites with hummocky cross-bedding, and finally, calcilutites and siltstones (rares). Those lithofacies represent platform sedimentary environment, in the shoreface-offshore transition. GPR (Ground Penetrating Radar) survey revealed depositional geometries such as sigmoidal, hummocky and parallel patterns. Petrographic analysis showed the presence of five carbonate microfacies and one hybrid terrigenous-carbonate: ooidal intraclastic grainstones, intraclastic grainstones, recrystallized grainstones, intraclastic wackestones, mudstones and laminated siltstones. Depositional environment of these rocks points to a deposition in a shallow marine carbonate platform, under storm waves influence, as identified in many tempestite cycles in the quarry. Structural analysis showed the presence of three fractures systems with principal directions N-S, NE-SW and NW-SE, subvertical in general, cutting the huge outcrop which present subhorizontal layers. Gamma-ray prospects allowed laterally correlate the four profiles prospected in the base of the quarry, and served as basis for a facies zoning that guided the 3D geological modelling of the quarry outcrop. The modelling used a workflow that interpolate microfacies data to define their spatial distribution and proportion along the entire outcrop. The results showed the predominance of oolitic intraclastic grainstones with about 58% of presence, followed by intraclastic grainstones with about 15%, siltites with 13%, wackestones with 12% and recrystallized grainstones with 2%. Carbonate lithofacies analysis, depositional architecture and geometry, in combination with micropetrographic data in thin section and textures observed in Scanning Electron Microscope (SEM), identified brittle structures, and modelled data suggests that the studied section of the Lagoa do Jacaré Formation in the GMD Quarry has a potential for a fractured non-conventional reservoir type.